2020
DOI: 10.1097/icb.0000000000000965
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Tears Due to Pickleball Injury

Abstract: Purpose: This is the first case series of two instances of retinal tears due to an injury sustained while playing pickleball.Methods: Case series.Results: A 66-year old white man presented with a symptomatic retinal tear, localized retinal detachment, and mild vitreous hemorrhage nine days after he was hit in his left eye while playing pickleball. The patient was not wearing eye protection while playing. The patient was treated with cryotherapy, and after three weeks, the vitreous hemorrhage and retinal detach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 2 publications
0
9
0
1
Order By: Relevance
“…Eye injuries in both sports makeup a very small proportion of all reported ED injuries, but they can and do happen and this review extends the number of such case reports by several fold. (12) Reviewing the narrative of each of the (n = 4 unweighted) cases showed that most pickleball eye injuries were caused by being hit with the ball and suggested that the pickleball eye injuries reported were generally less severe than the (n = 20 unweighted) tennis eye injuries. Eye injuries made up a higher proportion of all injuries among seniors playing tennis versus pickleball, 1.4% vs. 0.5% (weighted), respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eye injuries in both sports makeup a very small proportion of all reported ED injuries, but they can and do happen and this review extends the number of such case reports by several fold. (12) Reviewing the narrative of each of the (n = 4 unweighted) cases showed that most pickleball eye injuries were caused by being hit with the ball and suggested that the pickleball eye injuries reported were generally less severe than the (n = 20 unweighted) tennis eye injuries. Eye injuries made up a higher proportion of all injuries among seniors playing tennis versus pickleball, 1.4% vs. 0.5% (weighted), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the literature has focused on psychosocial, well-being and tness aspects. (6-8, 10, 11) Other than a few case reports, (12) there have been only three papers addressing injury risk: Greiner (2019), Quail (2019) and Forrester (2020). (1, 2, 13) Greiner published a short review that discussed injury aspects relative to other racquet sports.…”
Section: Importance Of Researchmentioning
confidence: 99%
“…An injury analysis conducted by the authors yielded 4 recent references which discussed pickleball injuries (2,15,34,35). A case-report analysis of an older pickleball athlete (age 71 years) presented a unique hamstring injury coupled with a full-width tear of the left adductor magnus tendon at its ischial attachment (34).…”
Section: Pickleball Needs Analysismentioning
confidence: 99%
“…The authors of this article noted that the adductor magnus can present similar mechanisms of potential injury as the hamstrings, such as strong eccentric contraction and/or sudden change in direction with forced adduction (34). Another article explored 2 injury cases of pickleball athletes (age 60 and 66 years, respectively) who sustained eye injuries because of a direct hit in the eye with a pickleball (2). Each player presented varying degrees of retinal detachment requiring treatment.…”
Section: Pickleball Needs Analysismentioning
confidence: 99%
See 1 more Smart Citation